Ecological niche differentiation of two salamanders (Caudata: Hynobiidae) from Hokkaido Island, Japan. Issue 2 (21st November 2020) - Tran, Dung Van; Terui, Shigeharu; Nomoto, Kazuhiro; Nishikawa, Kanto
Abstract: Understanding environmental factor determining ecological niche is very important to elucidating the distribution of species, and also revealing how closely related species are able to coexist in a particular region. Here, we applied ecological niche modeling to develop the ecological niches of two hynobiid salamanders: Salamandrella keyserlingii and Hynobius retardatus which are co‐occurring on Hokkaido Island, Japan. We, then, tested hypotheses about ecological niche differentiation between the two species. Our models showed that the potential distribution of S . keyserlingii was strictly limited to a small area at Kushiro Marsh, while the suitable distribution of H . retardatus was covered widely on Hokkaido Island. The results revealed the little geographic range overlap and the differentiation on the requirements of the ecological condition between the two species. We found nonequivalent niches in identity tests and counterintuitive results in background tests, indicating that S . keyserlingii has used a habitat subset of H . retardatus . Overall, our result contributed to understand the ecological niche space, and suggest the historical formation of these species on Hokkaido Island. The models can also be used to aid conservation purposes, such as habitat management, planning and designation of protected areas. Abstract : In this study, we applied ecological niche modeling approach to develop the ecological niches of two hynobiid salamanders of Salamandrella keyserlingii and Hynobius retardatus from Hokkaido Island, Japan. We also examined ecological niche similarities between these two species based on ENMtools.